The 20- and 100- dinar banknotes from 1905 - Pantelić Svetlana (Bankarstvo, 2015)
There are several characteristics identical for the 20- and 100-dinar banknotes: they bear the same date, i.e. 5 January 1905; it took some years to prepare them before releasing them into circulation; and the reason for their preparation was the need for smaller-denomination banknotes payable in gold and bigger-denomination banknotes payable in silver. The preparations for the printing of 20-dinar banknotes payable in gold lasted from 1892 until 1905. Their design was entrusted to Banque de France, and was completed according to the sketches and instructions of the unknown Serbian artists. The printing was finished by the end of 1906 when the first batch of these banknotes arrived from France. Although they bear the date of 5 January 1905, they were not put in circulation until 15 January 1907. It was being gradually withdrawn until 1934. In 1904 the National Bank passed the decision on issuing the 100-dinar banknote payable in silver, to be designed and printed by Banque de France. The banknote was put in circulation on 25 April 1907, and additional amounts were printed before, during and after the First World War, until 1924. It remained in circulation until 22 July 1938, although it was possible to exchange it afterwards at the National Bank and the Central State Treasury. This banknote is the favorite among the collectors worldwide, and is rather rare when it comes to its first-rate preservation quality.